2019
DOI: 10.1200/jco.2019.37.27_suppl.306
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvements in palliative radiotherapy at end of life: The FutRE Study.

Abstract: 306 Background: Palliative radiation therapy (RT) is offered to patients with cancer for symptom management. RT planning and delivery is resource intensive. Benefits may take weeks to develop. Palliative RT at the end of life may not be completed due to patient and disease factors. RT courses that are not completed may indicate a need for improved patient selection for RT and choice of RT prescription, minimizing the likelihood of delivering futile treatment. Methods: The FUTile Radiotherapy at End of life su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In other palliative clinical scenarios, treatment and prescribing decisions are dependent on the clinician's best judgement [7,8]. Investigators have shown differences in ROs' prescribing practices and that clinicians are inherently imperfect in their prognostication of patient survival [9][10][11][12][13]. Futile therapy is an intervention with a low probability of rendering an expected benefit to patients at a systems level [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In other palliative clinical scenarios, treatment and prescribing decisions are dependent on the clinician's best judgement [7,8]. Investigators have shown differences in ROs' prescribing practices and that clinicians are inherently imperfect in their prognostication of patient survival [9][10][11][12][13]. Futile therapy is an intervention with a low probability of rendering an expected benefit to patients at a systems level [14,15].…”
Section: Introductionmentioning
confidence: 99%